THE INFLUENCE OF LAMBADA ON TOURISM IN PORTO SEGURO IN THE 80’S AND 90’S - ASPECTS: SOCIOCULTURAL, GEOGRAPHIC, TOURIST AND ECONOMIC - Barbosa Ramos, Nairo (Revista Gênero e Interdisciplinaridade, 2023)
The lambada dance had an important cultural and economic impact in Porto Seguro, Bahia, Brazil, in the 1980s and 1990s. The dance attracted visitors from all over the world to the city, becoming one of the region’s main cultural attractions. The lambada also strengthened the identity and self-esteem of the local population, contributing to the cohesion and cultural strengthening of society. Dance has influenced Brazilian culture, including fashion, gastronomy and art. The cultural artistic manifestation “LAMBADA IMATERIAL CULTURAL PATRIMONY” made Porto Seguro an important tourist destination, being popularized all over the world through TV programs, films and shows. The city became known as the “Capital of Lambada ‘’ and many tourists were looking for places to dance, generating a demand for products and services related to lambada.